Paraguay : Report on the Observance of Standards and Codes; FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses assessment results on the observance of standards and codes on the Financial Action Task Force (FATF) recommendations for antimoney laundering and combating the financing of terrorism (AML/CFT) for Paraguay. The assessment reveals that the substantial U.S. dollar contraband trade that occurs on the borders shared with Argentina and Brazil facilitates money laundering in Paraguay. Achievements in the implementation of Paraguay's AML framework remain modest since the criminalization of the money laundering offence in 1996. The level of implementation and compliance with respect to the FATF recommendations is low in the financial sector.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet